2019
DOI: 10.3390/cells8010052
|View full text |Cite
|
Sign up to set email alerts
|

Mood Disorders, Accelerated Aging, and Inflammation: Is the Link Hidden in Telomeres?

Abstract: Mood disorders are associated with an increased risk of aging-related diseases, which greatly contribute to the excess morbidity and mortality observed in affected individuals. Clinical and molecular findings also suggest that mood disorders might be characterized by a permanent state of low-grade inflammation. At the cellular level, aging translates into telomeres shortening. Intriguingly, inflammation and telomere shortening show a bidirectional association: a pro-inflammatory state seems to contribute to ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 82 publications
0
30
0
Order By: Relevance
“…In our study, we reported significantly reduced LTL in patients with MDD compared to non‐psychiatric controls. The majority of studies published so far reported shorter telomeres in MDD patients compared to controls, while a smaller number showed no evidence for shorter TL in affected patients (Squassina et al, ). However, two recently published meta‐analyses, including 34,347 (Ridout, Ridout, Price, Sen, & Tyrka, ) and 7,207 subjects (Lin, Huang, & Hung, ), respectively, showed significantly shorter telomeres in depressed patients compared to controls, despite significant heterogeneity among studies (mainly dependent on different techniques to measure TL, source of used tissue and comorbid medical conditions).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we reported significantly reduced LTL in patients with MDD compared to non‐psychiatric controls. The majority of studies published so far reported shorter telomeres in MDD patients compared to controls, while a smaller number showed no evidence for shorter TL in affected patients (Squassina et al, ). However, two recently published meta‐analyses, including 34,347 (Ridout, Ridout, Price, Sen, & Tyrka, ) and 7,207 subjects (Lin, Huang, & Hung, ), respectively, showed significantly shorter telomeres in depressed patients compared to controls, despite significant heterogeneity among studies (mainly dependent on different techniques to measure TL, source of used tissue and comorbid medical conditions).…”
Section: Discussionmentioning
confidence: 99%
“…While some investigations reported opposite findings or no evidence, most of the studies converge on suggesting a role of TS in these disorders, including MDD. On the other hand, the effect of psychotropic medications on TL has been less investigated, and findings have been controversial for the most part, with the exception of lithium (Lindqvist et al, ; (Monroy‐Jaramillo et al, ; Muneer & Minhas, ; Squassina, Pisanu, Corbett, & Alda, ; Squassina, Pisanu, & Vanni, ).…”
Section: Introductionmentioning
confidence: 99%
“…A novel approach in our study is to ascertain the impact of the age-related medical comorbidities on such molecular dynamics. Previous research has shown that accelerated biological ageing is a hallmark of severe psychiatric disorders 43–45. Molecular signatures of this accelerated decay are currently being identified and point to TS as well as to a series of inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, chronic exposure to stressors leads to continuously higher perceived stress and subsequent stress arousal, which in turn remarkably influence telomere attrition ( Mathur et al, 2016 ). Other reports propose that inflammation plays a crucial role in telomere attrition and that continued stress is associated with the shorter TL and low-grade inflammation compared with healthy conditions without the presence of any inflammation ( Squassina et al, 2019 ).…”
Section: Biology Of Telomere and Effective Factorsmentioning
confidence: 99%